Sistema de criação de rotas automotivas virtuais para o tratamento de fobias de direção - Paiva, José Gustavo de Souza (2006)
Virtual Reality is a computational technique that allows user interactio n, immersion and navigation in virtual environments that simulates real life. Because of this reason, its use in several areas of the knowledge is very promising, especially in Psychology, in phobia treatment. For driving phobia treatment, these features can also bring benefits. There are several systems that use Virtual Reality for driving phobia treatment. In these systems, the patient covers virtual routes with elements that cause him this phobia. These systems, however, sin for not offering flexibility to the psychologist in the creation of routes, becoming the treatment limited to previously constructed routes, that nor always reveal adequate for the fears presented for the patients. This research shows the development of a route creation system to be used in driving phobia treatment, built to follow two basic principles: provide high flexibility to the psychologist, so he has freedom to create customized routes, according to each patient s profiles, and have a simple and intuitive interface, minimizing difficulties on the construction of these routes. Besides, this system maps a constructed 2D route to a virtual environment, automatically and transparent, excusing knowledge of computational techniques related to these operations. This interface makes possible to the psychologist choose amongst common objects, found on the traffic of cities, and locate them according to his necessities. Moreover, it allows that external conditions to the route to be configured, such as climatic and traffic conditions. The system was evaluated by a group of psychologists, whose majority did not have difficulties in using the system, and considered the process of construction of routes simple and intuitive. At the end, a series of future works is presented, that configures as functionalities to be added or modified on the system, conferring to it bigger efficiency in its function.